Crystal structure of (3,6-di(2-pyridyl)-4-phenylaminopyridazine-κ2N,N′)-bis(2-(p-toluene)pyridinyl-κ2C,N)-iridium(III) hexafluorophosphate –dichloromethane (1/1), C45H37Cl2F6IrN7P - Qian Jun; Ma Liang; Wang Yida (Zeitschrift für Kristallographie - New Crystal Structures)
C45H37Cl2F6IrN7P, monoclinic, P21/c (no. 14), a = 23.518(5) Å, b = 11.702(2) Å, c = 15.426(3) Å, β = 101.44(3)°, V = 4161.0(15) Å3, Z = 4, R gt(F) = 0.0474, wR ref(F 2) = 0.0924, T = 293 K.